Implementasi Model PjBL Untuk Meningkatkan Kreativitas Siswa Pada Pembelajaran SBdP Di Sekolah Dasar - ilmitriayuni23; Andi S. W. Ningrum; Nuri Nur Azizah; Hasnawati Hasnawati; Herlina Herlina; Kadek Herlina (JURNAL DIKDAS, 2025)
This research aims to analyze the application of the project-based learning model (Project-Based Learning, PjBL) in increasing student creativity in Arts, Culture and Crafts (SBdP) subjects in elementary schools. PjBL is an approach that involves students in real projects, so that it can stimulate their imagination and creativity. The research method used was a Systematic Literature Review (SLR) with a qualitative approach, which involved analysis of 24 relevant articles published in the last five years. The research results show that implementing PjBL significantly increases students' involvement, enthusiasm and creativity in creating works of art. However, challenges such as monotonous learning patterns and time constraints were also identified as obstacles in implementing this model. This research provides recommendations for overcoming these challenges to improve the quality of SBdP learning in elementary schools.